2017
DOI: 10.1136/rmdopen-2016-000364
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland ultrasound abnormalities in primary Sjögren’s syndrome: consensual US-SG core items definition and reliability

Abstract: ObjectivesUltrasonography (US) is sensitive for detecting echostructural abnormalities of the major salivary glands (SGs) in primary Sjögren’s syndrome (pSS). Our objectives were to define selected US-SG echostructural abnormalities in pSS, set up a preliminary atlas of these definitions and evaluate the consensual definitions reliability in both static and acquisition US-SG images.MethodsInternational experts in SG US in pSS participated in consensus meetings to select and define echostructural abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 37 publications
1
44
2
3
Order By: Relevance
“…However, the lack of a consensus scoring system complicates the incorporation of SGUS into the ACR/EULAR criteria. Jousse‐Joulin et al recently published an atlas with consensual definitions of SGUS abnormalities. The next step will be to agree on a consensus scoring system with a validated cutoff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of a consensus scoring system complicates the incorporation of SGUS into the ACR/EULAR criteria. Jousse‐Joulin et al recently published an atlas with consensual definitions of SGUS abnormalities. The next step will be to agree on a consensus scoring system with a validated cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…Many scoring systems are applied for SGUS, but recent analyses have shown that limiting scoring to hypoechogenic areas in both the submandibular and parotid gland on 1 side suffices for accurate differentiation between primary SS and non primary SS (18). Scoring of hypoechogenic areas showed good intra-and interobserver reliability (19,20). This reduction of the scoring system further increases the feasibility of the technique for common application in a diagnostic setting.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not yet established what the hypoechogenic areas reflect, echogenicity and homogeneity were identified as two reliable items, whereas the reliability of other core items was slight or poor. Parotid gland SGUS echogenicity provided substantial interobserver reliability with regard to suggested diagnosis of Sjögren's syndrome .…”
Section: Major Salivary Gland Ultrasonographymentioning
confidence: 98%
“…For diagnostic purposes, recent studies suggest that use of a simplified approach for SGUS evaluation of the major salivary glands may be sufficient. The reliability of SGUS was investigated in a two‐step process using both static and acquisition SGUS images . Selected SGUS echostructural abnormalities in Sjögren's syndrome (echogenicity, homogeneity, hyperechoic bands, number and location of hypo/anechoic areas, presence of abnormal lymph nodes in the glands, calcifications, visibility of posterior border, and diagnosis advice of primary Sjögren's syndrome based on the seven items) were defined and set up in a preliminary atlas.…”
Section: Major Salivary Gland Ultrasonographymentioning
confidence: 99%
“…In a recent study, an expert panel established that echogenicity and homogeneity are the parameters with the highest reproducibility and accuracy. While both pairs of parotid and submandibular glands should be examined, SGUS of the former was associated with better inter-rater reproducibility [48]. The OMERACT group published a consensus fourgrade semiquantitative scoring system (from 0 to 3) for the PGs and SMGs in patients with pSS was defined grade 0, normal parenchyma; grade 1, minimal change: mild inhomogeneity without anechoic/hypoechoic areas; grade 2, moderate change: moderate inhomogeneity with focal anechoic/hypoechoic areas; grade 3, severe change: diffuse inhomogeneity with anechoic/hypoechoic areas occupying the entire gland surface.…”
mentioning
confidence: 95%